Hygrothermal effects on the fatigue delamination growth onset in interlayer toughened CFRP joints - Gonzalez Ramirez, Francis Mariana (2020)
Aeronautic structures are exposed to a great variety of temperatures and humid environments during service. Nowadays, it is known that the combined influence of moisture and temperature induces further detrimental effects on the fatigue behavior of bonded joints when compared to the influence of each isolated condition. The effect of hygrothermal pre-conditioning on the fatigue delamination growth onset of different bonded technologies was investigated. This paper provides a material database for composite-joints tested under different environments and gives important insights on the failure mechanisms observed under cyclic loadings. This information can be latter used to validate analytical and numerical models.